Perbedaan Pemberian Core Stability Exercise dan Chair Based Exercise terhadap Peningkatan Fleksibilitas Lumbal Lansia - Ima Ratna Ramasari; Asita Rohmah Mutnawasitoh (Lembaga Pengembangan Kinerja Dosen, 2024)
Elderly people at the Kenanga 1 elderly posyandu who were given core stability exercises and chair base exercises. This type of quasi-experimental research is a two group pre and post test design approach, with a sample size of 50 people measured using the modified Schober test. From the test results using the wilcoxon sig value. Amoundted to 0,001(sig,<0,005) there wasan infulance of the core stability exercise treatment group, while the wilcoxon tets in the chair based exercise group resulted in a sig equal to 0,001(sig<0,005) there is influence on the chair based exercise treatment group. Man Whitney, a value of 0.210 (sig, > 0.05) was obtained, which means there was no difference in effect between the chair based exercise and core stability exercise groups. There is no significant difference between the core stability exercise and chair based exercise groups.